Simulation of the temperature in the process "friction stir welding"(fsw) of AA 1100-0 aluminum using the software ABAQUS/CAE (Publicaciones en Ciencias y Tecnología, 2012)
The work presented shows the simulated values of the temperatures experimentally undertaken in Blanco (2009) and Valdivé y Blanco (2012) during friction stir welding (FSW) of AA 1100-0 aluminum plates. This is done using the finite element method (FEM). We studied the behavior of temperature by applying MEF to the heat transfer equation used by Blanco (2009). The methodology used allowed modeling the problem using the software ABAQUS /CAE v6.7-1 with elements hexahedral of eight nodes and tetrahedral of four nodes. The simulation of the AA 1100-0 aluminum FSW reported a temperature diference of 80.3°C compared to the maximum value obtained experimentally by [1]. The result shows that the process modeling allows to predict the thermal behavior of the weld.
Keywords: Finite Element Method; Friction Stir Welding